2022
DOI: 10.1111/and.14499
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an animal model of ejaculatory duct obstruction

Abstract: This study aimed to establish animal models with different degrees of ejaculatory duct obstruction. Forty‐eight male rats aged 14–15 weeks were randomly divided into three groups (n = 16): control, complete ejaculatory duct obstruction (tied around the lower seminal vesicle gland and ductus deferens with a 2–0 silk ligature), and partial ejaculatory duct obstruction (padded with a wire guide). Mortality, complications, seminal vesicle morphology and histopathology were compared in the three groups at 4 and 8 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In our previous studies, we successfully established animal models of complete and partial obstruction of the ejaculatory duct [13]. Results indicated that rats in the complete EDO group exhibited progressive SVs, including reduced SV weight, SV atrophy, thinning of smooth muscle layer, and epithelial cell exfoliation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies, we successfully established animal models of complete and partial obstruction of the ejaculatory duct [13]. Results indicated that rats in the complete EDO group exhibited progressive SVs, including reduced SV weight, SV atrophy, thinning of smooth muscle layer, and epithelial cell exfoliation.…”
Section: Discussionmentioning
confidence: 99%
“…Rats in the control group were subjected to sham operation, without obstruction of the ejaculatory duct. For the detailed animal modeling protocol and pathology evaluation, please refer to our previous articles [13]. After surgery, rats were housed in an environment maintained at 12-hour light/12-hour dark cycle, a temperature of 23 °C with free access to standard diet and clean water ad libitum.…”
Section: Methodsmentioning
confidence: 99%